MAPPILA LITERATURE: THE TURN FROM RELIGION TO SOCIETY.THE ROLE OF MAPPILA POET PULIKKOTTIL HAIDER - Abinsha. M U (Indian Streams Research Journal, 2014)
Mappila Literature had a deviation in its theme and language selection in the beginning of 20 th Century. It become more popular and secular by selecting social issues as its theme.Pulikkottil haider is the of such Change.